The Stone Age - Netzley, Patricia D. (San Diego, CA : Lucent Books, 1998)
Discusses the long period of human history known as the Stone Age during which humans evolved into beings capable of inventing and using increasingly sophisticated tools and creating complex social groupings.
Includes bibliographical references (p. 88-90) and index.
Keywords: Stone age -- Juvenile literature; Prehistoric peoples -- Juvenile literature; Human evolution -- Juvenile literature; Stone age; Prehistoric peoples; Evolution